1996
DOI: 10.1002/(sici)1097-0010(199601)70:1<89::aid-jsfa470>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

TheDMACA-HCl Protocol and the Threshold Proanthocyanidin Content for Bloat Safety in Forage Legumes

Abstract: A protocol using HCl‐acidified 4‐dimethylaminocinnamaldehyde (DMACA) was developed for screening proanthocyanidins (PA) in plants. Individual PA‐containing cells could be observed following staining of decolourised leaves with DMACA. The quantitative assay using DMACA‐HCl to detect soluble PA and butanol–HCl to detect insoluble PA could detect PA content lower than 0·4 mg g−1 dry matter (DM). The DMACA–HCl protocol is recommended for PA detection in low‐PA plants because of its higher sensitivity than vanillin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
300
1
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 393 publications
(310 citation statements)
references
References 17 publications
(39 reference statements)
2
300
1
3
Order By: Relevance
“…The results were expressed as rutin equivalents. The total flavanol and flavans content (TFAC) was detected with p-DMACA (Li et al, 1996). The results were expressed as (+)-catechin equivalents.…”
Section: Determination Of Total Phenolicssupporting
confidence: 77%
“…The results were expressed as rutin equivalents. The total flavanol and flavans content (TFAC) was detected with p-DMACA (Li et al, 1996). The results were expressed as (+)-catechin equivalents.…”
Section: Determination Of Total Phenolicssupporting
confidence: 77%
“…The sensitivity of the DMACA stain (another aromatic aldehyde) is some 4-fold greater than vanillin, and has been used to detect PA in plant species previously thought to lack PA when tested using vanillin stain (Li et al, 1996). Another advantage of DMACA over vanillin is that DMACA stains PA blue-purple, whereas vanillinstained PA is pink and can be confused with pink anthocyanin pigments in tissues containing both compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in this investigation, all of the tannin extracts were analysed by HPLC-phloroglucinolysis without further purification to maintain a consistent approach. Another approach would have been to use solid phase extraction, but dimethylcinnamaldehyde staining (Li et al, 1996) indicated that some tannin material was usually retained on these columns and this was not pursued further.…”
Section: Tannin Polymer Lengthmentioning
confidence: 99%